Binder, positive pole piece and secondary battery

By developing a high-adhesion and low swelling rate binder without fluorine, the problems of secondary battery electrode sheet expansion and environmental pollution are solved, and the effect of improving the energy density of secondary battery is achieved.

CN119552602APending Publication Date: 2025-03-04NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411745966.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The electrode sheet of the existing secondary batteries is prone to expand after charging and discharging, affecting the energy density. The binder PVDF used contains fluorine elements, which is highly polluted to the environment.

Method used

A binder that is basically free of fluorine elements has been developed. By using the binder in the positive electrode sheet and the secondary battery, the expansion of the electrode sheet is suppressed and the energy density of the secondary battery is increased. The binder consists of a first polymer, including specific amide groups, cyano groups and flexible long carbon chains, with high bonding and low swelling.

Benefits of technology

By using this binder, the expansion rate of the positive electrode sheet is significantly reduced, the energy density of the secondary battery is improved, and it has environmental advantages because it does not contain fluorine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552602A_ABST
    Figure CN119552602A_ABST
Patent Text Reader

Abstract

The invention provides a binder, a positive pole piece and a secondary battery. The adhesive comprises a first polymer as shown in a formula I, R1 is C5-C12 alkyl, and R2 is any one of C1-C3 alkyl, a hydrogen atom or aryl; the number average molecular weight of the first polymer is 6 * 10 < 4 >-2 * 10 < 6 >. The binder disclosed by the invention basically does not contain a fluorine element, is low in swelling rate and high in binding power, and can inhibit the expansion of the positive pole piece and improve the energy density of the secondary battery when being used in the positive pole piece and the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of secondary batteries, and in particular to a positive electrode material, a positive electrode sheet and a secondary battery. Background Art

[0002] The electrode plates of secondary batteries such as lithium-ion batteries include a current collector and an active layer on the surface of the current collector. After charging and discharging, the thickness of the electrode plates of secondary batteries expands and rebounds greatly; the thickness expansion rebound of the positive electrode plates after charging and discharging is approximately 5% of the original base thickness, and the thickness expansion rebound of the anode plates after charging and discharging is approximately 20%. Under the condition of limited battery thickness, if the expansion rebound of the plate thickness can be reduced, the bare battery cell can be wound with one or more layers of plates, which can significantly increase the battery volume energy density.

[0003] Currently, PVDF (polyvinylidene fluoride) is used as a binder to improve the bonding strength between the layers in the electrode, thereby inhibiting the expansion of the electrode and improving the energy density of the secondary battery. However, the fluorine element in PVDF will pollute the environment and is not conducive to environmental protection. Therefore, there is an urgent need for a solution that can replace PVDF to inhibit the expansion of the electrode. Summary of the invention

[0004] The present application can provide a binder, a positive electrode sheet and a secondary battery. The binder of the present application basically does not contain fluorine element, and has a low swelling rate and high bonding strength, which can improve the bonding strength of the positive electrode sheet, inhibit the expansion of the positive electrode sheet, and improve the energy density of the secondary battery.

[0005] In a first aspect, the present application provides a binder, which includes a first polymer, and the first polymer includes a structure shown in the following formula I:

[0006]

[0007] wherein R1 is a C5-C12 alkyl group, R2 is any one of a C1-C3 alkyl group, a hydrogen atom or an aryl group; the number average molecular weight of the first polymer is 6 x 10 4 ~2x10 6 .

[0008] In the above technical solution, the inventors found that when the number average molecular weight of the first polymer is limited to 6 x 10 4 ~2x10 6 When the binder is used in a secondary battery, the amide group in the first polymer can make the binder have excellent dispersibility and adhesion through the dual effects of dipole-dipole and intermolecular hydrogen bonding; the cyano group in the first polymer is a strong polar group with a short bond length, which not only makes the binder have good high voltage stability, but also when the binder is used in a secondary battery, the cyano group in the first polymer can also play a role in conducting Li +and protect the positive electrode material; the main chain of the first polymer has a flexible long carbon chain such as the R1 group, which can make the first polymer have good flexibility, which can not only further enhance the bonding force of the binder, but also make the binder have good elasticity. Therefore, the binder in the present application not only has good bonding force, but also has a low swelling rate; in addition, the binder in the present application basically does not contain fluorine elements, which is also beneficial to environmental protection.

[0009] In a possible implementation, the binder satisfies at least one of the following conditions: (1) R1 is a C5-C8 alkyl group; (2) 500≤m≤20000; (3) 300≤n≤10000; (4) 1.25n≤m≤3n; (5) the number average molecular weight of the first polymer is 3x10 5 ~2x10 6 .

[0010] In the above technical solution, the adhesive has higher bonding force and lower swelling rate.

[0011] In a possible implementation, the adhesive satisfies at least one of the following conditions: (1) 800≤m≤13960; (2) 400≤n≤10000.

[0012] In one possible implementation, the polydispersity of the first polymer is 1.3 to 1.5.

[0013] In the above technical solution, the polydispersity is in the range of 1.3 to 1.5, and the properties of the first polymer are relatively uniform, which can better improve the bonding force of the binder and reduce the swelling rate of the binder.

[0014] In a possible implementation, based on infrared spectroscopy characterization, the first polymer has a wavelength of 1100 cm -1 ~1300cm -1 There are characteristic peaks inside.

[0015] In a possible implementation, the glass transition temperature of the first polymer is -45°C to -25°C.

[0016] In a second aspect, the present application provides a positive electrode plate, which includes a positive electrode current collector, at least one surface of which is provided with a positive electrode active layer, and the positive electrode active layer includes the above-mentioned binder. Therefore, the positive electrode plate of the present application also has good performance.

[0017] In a possible implementation, based on the mass of the positive electrode active layer, the mass content of the binder is a%, and 0.5≤a≤2.

[0018] In the above technical solution, the mass content of the binder is within the above range, which can ensure that the positive electrode sheet has a lower expansion rate and also basically has no adverse effect on the energy density of the positive electrode sheet.

[0019] In a possible implementation, the positive electrode active layer further includes a positive electrode active material and a positive electrode conductor. The positive electrode conductor is attached to the surface of the positive electrode active material. The coverage rate of the positive electrode conductor on the surface of the positive electrode active material is S%, and 73.6+2a≤S<83.7.

[0020] In the above technical solution, the binder can make the conductive agent adhere to the surface of the positive electrode active material, which is beneficial to improve the conductivity of the positive electrode sheet. The coverage of the conductive agent on the surface of the positive electrode active material meets the above conditions, which is beneficial to the deintercalation of lithium ions from the positive electrode active material.

[0021] In a possible implementation, the positive electrode active material contains a transition metal element.

[0022] In the above technical solution, the nitrile functional groups in the binder can form a complex adsorption structure with the ions of the transition metal elements, so that the structure of the positive electrode active material is not easily destroyed, and the thermal safety performance of the positive electrode plate can be improved.

[0023] In a possible implementation manner, the transition metal element includes at least one of nickel, cobalt, or manganese.

[0024] In one possible implementation, the coating density of the binder on at least one surface of the positive electrode sheet is 0.129 mg / mm 2 ~0.228mg / mm 2 .

[0025] In the above technical solution, the bonding retention rate of the positive electrode plate is high, the structure is relatively stable, and the service life is long.

[0026] In a third aspect, the present application provides a secondary battery, which includes the above-mentioned positive electrode plate. Therefore, the secondary battery provided by the present application has a higher energy density.

[0027] Beneficial effects of this application:

[0028] The present application provides a binder, a positive electrode plate and a secondary battery. The binder of the present application includes a first polymer, and the first polymer includes a structure shown in Formula I. In the first polymer, a cyano group, an amide group and an R1 group of the main chain work together to make the binder have good bonding force and a low swelling rate. When the binder is used in a positive electrode plate and a secondary battery, the expansion of the positive electrode plate can be suppressed and the energy density of the secondary battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 This is the infrared spectrum of the first polymer in Example 1-1 of the present application. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0032] In the prior art, after charging and discharging, the pole piece of the secondary battery is prone to expansion, which is not conducive to the energy density of the secondary battery; although the pole piece expansion can be suppressed by using PVDF in the binder, the fluorine element contained in PVDF causes great pollution to the environment. In order to replace PVDF, the expansion is suppressed by thinning the aluminum foil and increasing the compaction density of the pole piece, but the thinning of the aluminum foil is prone to breakage and wrinkling; too high a compaction density will make the pole piece brittle and easy to break, and will also cause poor electrolyte infiltration, resulting in low capacity and lithium precipitation.

[0033] Based on the above technical problems, the present application provides a binder with low swelling rate, high bonding force, and basically no fluorine element. When used in positive electrode sheets and secondary batteries, it can inhibit the expansion of the electrode sheets and improve the energy density of the secondary battery. The technical solution of the present application is described in detail below:

[0034] In a first aspect, the present application provides a binder, which includes a first polymer, and the first polymer includes a structure shown in the following formula I:

[0035]

[0036] wherein R1 is a C5-C12 alkyl group, R2 is any one of a C1-C3 alkyl group, a hydrogen atom or an aryl group; the number average molecular weight of the first polymer is 6 x 10 4 ~2x10 6 , preferably 3 x 10 5 ~2x10 6 .

[0037] In the binder of the present application, the first polymer basically does not contain fluorine, which is beneficial to environmental protection. Compared with other groups, the amide group in the first polymer can make the binder have very excellent adhesion and dispersibility through the two effects of dipole-dipole and intermolecular hydrogen bonding; the cyano group in the first polymer is a strong polar group with a short bond length, which not only makes the binder have good high voltage stability, but also when the binder is used in a secondary battery, the cyano group in the first polymer can also play a role in conducting Li + and protect the positive electrode material. In addition, since the main chain of the first polymer also has a flexible long carbon chain such as the R1 group, the first polymer can have good flexibility, which can not only further enhance the bonding force of the binder, but also make the binder have good elasticity; preferably, the R1 group can be a straight chain alkyl or a C5-C8 alkyl, such as a straight chain C5 alkyl. In addition, the side chain R2 connected to the amide group can be any one of a C1-C3 alkyl, a hydrogen atom or an aromatic group, so that its chain length is shorter, the steric effect can be controlled to reduce the risk of agglomeration and sedimentation of the binder, so the R2 group is preferably any one of a C1-C3 alkyl or a hydrogen atom.

[0038] It should be noted that in the binder of the present application, the first polymer is usually obtained by homopolymerizing two different monomers to obtain two homopolymers, and then connecting the two homopolymers. The two monomers are monomers corresponding to the structural units of the first polymer, that is, one of the monomers is acrylonitrile and the other monomer is The monomer corresponding to the structural unit, and in the process of homopolymerization of the monomer, the types of R1 and R2 do not have to be exactly the same, as long as they meet the scope of the general formula. The present application does not limit the homopolymer and the specific reaction steps for connecting two homopolymers, as long as the purpose of the present application can be achieved. In addition, in order to make the number average molecular weight of the first polymer between 6×10 4 ~2x10 6 As an example, in some embodiments of the present application, 500≤m≤20000, preferably 800≤m≤13960, specifically 500, 600, 800, 1000, 5000, 10000, 13960, 20000, 36926, etc., or within the range of any two of the above values; 300≤n≤10000, preferably 400≤n≤10000, specifically 300, 350, 400, 800, 1000, 5000, 10000, 15274, etc., or within the range of any two of the above values.

[0039] In addition, in some embodiments of the present application, in order to further enhance the bonding strength of the adhesive and reduce its swelling rate, m and n may satisfy the following relationship: 1.25n≤m≤3n.

[0040] In order to improve the uniformity of the binder, thereby further improving the adhesive force of the binder and reducing the swelling rate of the binder, in some embodiments of the present application, the polydispersity of the first polymer is generally 1.3 to 1.5.

[0041] In addition, the first polymer in the binder can also be determined based on infrared spectroscopy or glass transition temperature. Specifically, based on infrared spectroscopy characterization, with amide group as a special reference functional group, the first polymer has a temperature of 1100 cm -1 ~1300cm -1 There are characteristic peaks; based on DSC (Differential Scanning Calorimeter) characterization, the glass transition temperature of the first polymer is -45°C to -25°C.

[0042] In a second aspect, the present application provides a positive electrode plate, which includes a positive electrode current collector, at least one surface of the positive electrode current collector is provided with a positive electrode active layer, and the positive electrode active layer includes the above-mentioned binder.

[0043] It should be noted that, in the present application, "a positive electrode active layer disposed on at least one surface of the positive electrode current collector" means that the positive electrode active layer can be disposed on one surface in the thickness direction of the positive electrode current collector, or on two surfaces in the thickness direction of the positive electrode current collector. Moreover, in the present application, the "surface of the positive electrode current collector" can be the entire area of ​​the positive electrode current collector, or it can be a partial area of ​​the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. As an example, in some embodiments of the present application, on the surface coated with the positive electrode active layer, the coating density of the binder is 0.129 mg / mm 2 ~0.228mg / mm 2 At this time, the bonding retention rate f of the adhesive can reach 0.95 to 1. The specific method for measuring the bonding retention rate can be found in the subsequent content of this application.

[0044] In the positive electrode sheet of the present application, the positive electrode active layer contains a binder, which can improve the bonding force between the positive electrode active layer and the positive electrode current collector in the positive electrode sheet and reduce the swelling rate of the positive electrode active layer in the positive electrode sheet. Specifically, the swelling rate of the positive electrode sheet can be measured in the following way:

[0045] Select a positive electrode sheet with an initial resistance R1 of 0.005Ω to 1Ω and an initial weight W1 of 5g to 90g. After soaking the positive electrode sheet in an 85°C oven for 48 hours, measure the second resistance R2 and the second weight W2 of the positive electrode sheet; R2 will be in the range of 0.001Ω to 0.9Ω, W2 will be in the range of 8g to 100g, and at this time the four parameters will satisfy the following relationship: This shows that the positive electrode has high adhesion and low swelling rate. There is also an empirical formula: the electrolyte retention of the positive electrode increases by 1wt%, and its resistance decreases by 0.02Ω. The maximum liquid absorption mass percentage of the electrolyte of the positive electrode of this application does not exceed 30%, from which the above relationship is derived. The specific measurement methods of resistance and weight can be found in the subsequent content of this application.

[0046] In the positive electrode sheet, in addition to the binder, the positive electrode active layer also includes positive electrode active materials, conductive agents, etc. The mass of the binder is generally 0.5% to 2% of the mass of the positive electrode active layer, and can be specifically 0.5%, 1%, 1.5%, 2%, etc. or within the range of any two of the above values. Compared with other binders, the present application only requires 0.5% to 2% of the binder to well suppress the expansion of the positive electrode sheet, which will not reduce the content of the positive electrode active material, and will not easily cause the energy density loss of the secondary battery. In addition, the inventors have also found that the higher the amount of binder added in the positive electrode sheet, the higher the temperature at which the secondary battery can pass the thermal shock when the secondary battery is subsequently made. Under a high voltage system (not less than 4.5V), the highest thermal shock test that lithium cobalt oxide and the ternary system can pass is 140°C.

[0047] In the positive electrode sheet of the present application, the positive electrode active material can be any material that can reversibly embed and de-embed Li + 、Na + The positive electrode sheet and the secondary battery can be charged and discharged normally; and in the positive electrode sheet of the present application, the amide group in the first polymer of the binder will generate hydrogen bonds with the positive electrode material, thereby further enhancing the bonding force between the positive electrode active layer and the positive electrode current collector. The positive electrode active material includes but is not limited to lithium cobalt oxide (LiCo O2), and it may also include but is not limited to at least one of lithium iron phosphate (LiFePO4), lithium manganese oxide, lithium nickel oxide, ternary materials, etc., and ternary materials include but are not limited to LiNi x Co y Mn z O2、LiNi x Co y Al z O2, etc., and the content of Ni, Co, Mn, Al, etc. can be adjusted to ensure that x+y+z=1. For example, the ternary material can be LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.88 Co 0.08 Mn 0.04 O2、LiNi 0.8 Co 0.15 Mn 0.05 O2、LiNi 0.8 Co0.1 Mn 0.1 O2、LiNi 0.88 Co 0.1 Mn 0.02 O2、LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.88 Co 0.1 Al 0.02 O2, etc.

[0048] In some embodiments of the present application, a positive electrode active material containing a transition metal element is preferred. The transition metal element may be at least one of nickel, cobalt or manganese; for example, it may be lithium cobalt oxide, a ternary material, etc. This can improve the thermal safety performance of the positive electrode plate and the secondary battery. The principle is that the first polymer of the binder is rich in nitrile functional groups, and the nitrile functional groups can form a complex adsorption structure with the ions of the transition metal elements (such as cobalt ions, etc.), inhibiting the dissolution of metal ions and ensuring that the structure of the positive electrode active material is not easily destroyed. In this way, the oxygen atoms in the positive electrode active material are not easy to overflow to produce oxygen, thereby reducing the probability of thermal runaway at high temperatures.

[0049] The present application has no restrictions on the type of positive electrode conductive agent, and any known conductive material can be used. Specifically, the positive electrode conductive agent includes, but is not limited to, carbon black such as acetylene black, Super-P, or amorphous carbon such as needle coke, or carbon nanotubes, or at least one of graphene and the like. Due to the presence of the binder, in the present application, the positive electrode conductive agent will adhere to the surface of the lithium cobalt oxide particles, and the coverage of the positive electrode conductive agent on the surface of the lithium cobalt oxide is S%, and the coverage S% and the content a% of the binder generally satisfy the following relationship: 73.6+2a≤S<83.7, so that the carbon nanotubes can be evenly distributed in the positive electrode active layer, which is beneficial to the deintercalation of lithium ions from positive electrode active materials such as lithium cobalt oxide.

[0050] In addition, the positive electrode sheet of the present application will also add resin additives according to actual needs to further improve the safety performance of the positive electrode sheet, and the resin additives include but are not limited to at least one of melamine formaldehyde resin, phenolic resin, epoxy resin and its derivatives. The present application has no special restrictions on the type and amount of resin additives, as long as they can meet the purpose of the present application.

[0051] In the positive electrode sheet, the type of positive current collector is not particularly limited, and it can be any material known to be suitable for use as a positive current collector. The material of the positive current collector includes, but is not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, and tantalum. In addition, in order to reduce the electronic contact resistance between the positive current collector and the positive active layer, a conductive additive or a conductive coating may be provided on the surface of the positive current collector. The conductive additive includes, but is not limited to, carbon and precious metals such as gold, platinum, and silver. The conductive coating may be a mixture layer of an inorganic oxide, a conductive agent, and a positive electrode binder.

[0052] When preparing the positive electrode sheet, the components in the positive electrode active layer can be dissolved or dispersed in a liquid solvent to prepare a positive electrode slurry, and then the positive electrode slurry is coated on the positive electrode collector and dried to form a positive electrode active layer on the positive electrode collector, thereby obtaining a positive electrode sheet. When using this method to prepare the positive electrode sheet, there is no special restriction on the solvent in the positive electrode slurry, as long as it can dissolve or disperse the above components. Specifically, the solvent in the positive electrode slurry includes but is not limited to N-methylpyrrolidone (NMP), ethylene carbonate (EC), etc. In addition, when preparing the positive electrode sheet, the components in the positive electrode active layer can also be dry mixed to form a sheet, and then the obtained sheet is crimped to the positive electrode collector.

[0053] In a third aspect, the present application provides a secondary battery, which includes the above-mentioned positive electrode plate. Since the positive electrode plate in the secondary battery of the present application is not easy to expand and rebound after charging and discharging, the secondary battery of the present application has excellent energy density.

[0054] In the secondary battery of the present application, the positive electrode sheet is specifically as shown in the above content of this article, and the other structures are specifically as follows:

[0055] Negative electrode

[0056] The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one surface of the negative electrode current collector, and the components of the negative electrode active layer include a negative electrode sheet active material. That is, in the present application, the negative electrode active layer can be disposed on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. Moreover, in the present application, the "surface of the negative electrode current collector" can be the entire area of ​​the negative electrode current collector, or it can be a partial area of ​​the negative electrode current collector. The present application has no special restrictions, as long as the purpose of the present application can be achieved.

[0057] The negative electrode active layer generally contains negative electrode sheet active materials, and the present application does not have any particular restrictions on the negative electrode sheet active materials. Specifically, the negative electrode sheet active materials may include at least one of carbon materials or silicon-based materials. More specifically, carbon materials include but are not limited to at least one of natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon or soft carbon; silicon-based materials include but are not limited to at least one of silicon, silicon-oxygen composite materials or silicon-carbon composite materials.

[0058] In some embodiments, the negative electrode active layer generally further contains a negative electrode sheet conductive agent. The present application has no particular restrictions on the type of the negative electrode sheet conductive agent, as long as it can achieve the purpose of the present application. For example, the negative electrode sheet conductive agent includes but is not limited to at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots or graphene.

[0059] In some embodiments, the negative electrode active layer may also contain a negative electrode binder and a thickener. The present application has no particular restrictions on the types of the negative electrode binder and the thickener, as long as the purpose of the present application can be achieved. For example, the negative electrode binder may include but is not limited to at least one of polyvinyl alcohol, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber or acrylic (ester) styrene-butadiene rubber; the thickener in the negative electrode slurry may include but is not limited to at least one of sodium carboxymethyl cellulose or lithium carboxymethyl cellulose.

[0060] In the negative electrode sheet, the material of the negative electrode current collector includes but is not limited to copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc., and there is no special limitation in this application. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide).

[0061] In addition, in the present application, there is no particular limitation on the thickness of the negative electrode current collector and the negative electrode active layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 12 μm, and the thickness of the single-sided negative electrode active layer is 30 μm to 160 μm.

[0062] In addition, similar to the preparation of the positive electrode sheet, when preparing the negative electrode sheet, it can be configured into a negative electrode slurry, and then the negative electrode slurry is coated on the negative electrode collector and dried to form a negative electrode active layer on the negative electrode collector to obtain a negative electrode sheet; or the components in the negative electrode active layer can be dry mixed to form a sheet, and then the obtained sheet is pressed onto the negative electrode collector to form a negative electrode active layer, thereby obtaining a negative electrode sheet. The solvent in the negative electrode slurry includes any one of an aqueous solvent and an organic solvent. The aqueous solvent includes but is not limited to a mixed solvent of alcohol and water or water. Organic solvents include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide. In addition, in some other embodiments, when using an aqueous solvent, the components of the negative electrode slurry will also include a thickener and styrene-butadiene rubber (SBR) emulsion to slurry the negative electrode slurry, thereby adjusting the viscosity of the negative electrode slurry. The types of thickeners in the positive electrode slurry include, but are not limited to, at least one of carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and their salts.

[0063] Electrolyte

[0064] The electrolyte can transport lithium ions and electrons to ensure the formation of a pathway inside the secondary battery. The electrolyte usually contains lithium salts, solvents and additives. It should be noted that the present application does not have any specific restrictions on the amount of each component in the electrolyte, as long as the purpose of the present application can be achieved.

[0065] Specifically, the lithium salt can be dissolved in a solvent to form an ion conductor, used as a conductive medium and a lithium ion transmission medium; the lithium salt includes but is not limited to at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(oxalatoborate), lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorooxalatoborate), lithium bis(fluorosulfonylimide), and the like.

[0066] The solvent can dissolve the lithium salt and the additive, and the solvent can be at least one of carbonate, carboxylic acid ester, ether, alcohol, etc., wherein the carbonate can be divided into cyclic carbonate, linear carbonate, etc. Cyclic carbonate specifically includes but is not limited to at least one of ethylene carbonate, propylene carbonate, etc.; linear carbonate specifically includes but is not limited to at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, etc.; carboxylic acid ester includes but is not limited to at least one of methyl formate, methyl acetate, methyl butyrate, ethyl propionate, propyl propionate, propyl acetate, etc.; ethers include but are not limited to at least one of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, etc.; alcohols include but are not limited to at least one of ethanol, ethylene glycol, glycerol, etc.

[0067] The additives include, but are not limited to, nitriles, sulfones, sulfoxides, fluoronitriles, fluoroesters, and the like.

[0068] Isolation film

[0069] In order to prevent short circuit, a separator is usually provided between the positive electrode sheet and the negative electrode sheet. In this case, the electrolyte of the present application is usually used by infiltrating the separator.

[0070] There is no particular restriction on the material and shape of the isolation membrane, as long as the effect of the present application is not significantly impaired. The material of the isolation membrane may be a resin, glass fiber, inorganic substance, etc. formed by a material that is stable to the electrolyte of the present application. In some embodiments, the isolation membrane includes a porous sheet or a non-woven fabric-like material with excellent liquid retention. Examples of materials for resin or glass fiber isolation membranes include but are not limited to polyolefins, aromatic polyamides, polyimides (PI), polyamides (PA), polytetrafluoroethylene, polyether sulfone, spandex or aramid, etc. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above isolation membranes can be used alone or in any combination.

[0071] The separator may also be a material formed by laminating the above materials, examples of which include, but are not limited to, a three-layer separator formed by laminating polypropylene, polyethylene, and polypropylene in this order.

[0072] The materials of the inorganic substance include, but are not limited to, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates (eg, barium sulfate, calcium sulfate, etc.). The form of the inorganic substance includes, but is not limited to, granular or fibrous forms.

[0073] The separator may be in the form of a thin film, including but not limited to non-woven fabrics, woven fabrics, microporous films, etc. In the thin film form, the pore size of the separator is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In addition to the above-mentioned independent thin film separators, the following separators can also be used: a separator formed by forming a composite porous layer containing the above-mentioned inorganic particles on the surface of the positive electrode and / or the negative electrode using a resin-based adhesive, for example, a separator formed by using fluororesin as an adhesive to form a porous layer on both sides of the positive electrode with 90% of the aluminum oxide particles having a particle size less than 1 μm.

[0074] The thickness of the separator is arbitrary. In some embodiments, the thickness of the separator is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the separator is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the separator is within the above range, insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the secondary battery can be ensured.

[0075] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, for example, it may be at least one of the aforementioned binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).

[0076] The secondary battery of the present application also includes a packaging bag for containing a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.

[0077] The use of the secondary battery of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the secondary battery of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.

[0078] Example

[0079] The following uses lithium-ion batteries as an example to illustrate the present application in more detail with examples and comparative examples. Those skilled in the art will understand that the preparation method described in the present application is only an example, and any other suitable preparation method is within the scope of the present application.

[0080] Test methods and equipment:

[0081] Adhesion test

[0082] (1) The secondary battery cell is discharged to 3V at 25°C and a low current (0.2C) to perform a full discharge process. After the full discharge process is completed, the positive electrode plate is removed from the fully discharged cell with a voltage of 3V in an environment of 25°C, and then the residual electrolyte on the surface of the plate is wiped off with dust-free paper.

[0083] (2) Test the adhesive strength of the removed positive electrode sheet under a universal tensile testing machine as follows: first, use a blade to cut a sample with a width of 30 mm and a length of 100 mm to 160 mm. Then, stick the double-sided tape on the steel plate with a width of 20 mm and a length of 90 mm to 150 mm. Stick the cut electrode sample on the double-sided tape with the test surface facing down. Then, stick the green glue (width 20 mm and length 90 mm to 150 mm) tightly on the surface of the electrode. Then, insert a paper tape with a width equal to that of the electrode and a length greater than the length of the sample (80-200 mm) under the green glue and fix it with wrinkled glue. Finally, turn on the tensile testing machine, adjust the limit block to the appropriate position, and record the value of the tensile testing machine.

[0084] Adhesion retention test

[0085] The secondary battery is disassembled after the 45°C cycle test, the positive electrode sheet is taken out and the adhesion of the positive electrode sheet is tested, recorded as F1, and then the positive electrode sheet, graphite anode and ceramic isolation membrane are made into a single-layer laminated battery cell, and 0.2C charge and 0.2C discharge cycles are performed; after 200 cycles, the single-layer laminated battery cell is disassembled and the adhesion of the positive electrode sheet is tested, recorded as F2, and then the adhesion retention rate f is calculated using the following formula: f=F1 / F2.

[0086] Resistance test

[0087] (1) Obtain the positive electrode sheet using the method in step (1) of the "Adhesion Test".

[0088] (2) Use a film resistor (manufactured by Yuanneng Technology) to test the resistance of the sample to be tested. Before testing, wipe the test probe of the film resistor with alcohol, and then return the pressure and resistance to zero. Place the cut positive electrode sheet (60mm×80mm) flat on the sample stage, and then place the sample stage in the test chamber. Take 12 different positions of each positive electrode sheet sample for testing, and then calculate the average value to obtain the resistance of the positive electrode sheet in Ω.

[0089] Weight and resistance test

[0090] Get a fully charged positive electrode sheet (see "Adhesion Test" for how to get it), air-dry the electrolyte on the surface of the positive electrode sheet, and test the initial weight and initial resistance; then immerse the positive electrode sheet in the electrolyte, bake it in an 85°C oven for 48 hours, and then test the second weight and second resistance. The rate of change in weight can represent the swelling rate of the binder and the expansion rate of the positive electrode sheet.

[0091] Test of the coverage of conductive agent on the surface of positive electrode active material

[0092] (1) Obtain the positive electrode sheet using the method in step (1) of the "Adhesion Test".

[0093] (2) Use a surface Brewster film meter to test coverage: Divide the narrow side of the pole piece into three equal parts, select the upper left corner area of ​​each part, cut 1pcs of 2mm*2mm square pole piece, place the sample on the measuring table, ensure that the incident light is perpendicular to the sample surface, record the intensity of the reflected light, pay attention to the maximum value of the light intensity, and obtain the light intensity reflectivity through the measured light intensity change. Calculate the coverage based on the measured reflectivity change and the known Brewster angle conditions.

[0094] Energy density test

[0095] Charge the prepared, formed and aged cells from 3V to 4.51V at 0.2C at room temperature (25°C), leave for 5 minutes, and then discharge from 4.51V to 3V at 0.2C. Record the discharge capacity and discharge platform voltage. Measure the cell volume of the fully discharged cell using the water displacement method and record the data.

[0096] Energy density = capacity * platform voltage / cell volume, unit is Wh / L.

[0097] Infrared spectroscopy characterization

[0098] (1) Obtain binder powder using the method of step (1) in the “polydispersity test”.

[0099] (2) 2 mg of binder powder is taken and pressed into tablets using a potassium bromide tabletting method. The tablets are then placed in a Fourier transform infrared spectrometer for testing to obtain an infrared spectrum of the binder.

[0100] Polydispersity test

[0101] (1) Preparation of binder powder: Fully discharge the positive electrode under 25°C (see "Bonding Test" for full discharge process), then remove the positive electrode and wipe off the residual electrolyte on the surface of the electrode with dust-free paper. Then soak the positive electrode in dimethyl carbonate for 1 hour, then take it out and air dry it in a fume hood. After air drying, perform the following operations:

[0102] First, the pole piece is immersed in 500mL of N-methylpyrrolidone (NMP), and a single-rod stirrer is used at 1500r / min for 4h to fully disperse the coating layer on the aluminum foil into the NMP to form a uniform slurry. Secondly, a suction filtration device with a filter paper pore of 100nm is used to remove the solid matter in the slurry, leaving a clear NMP solution, and then the resulting liquid is placed in a 120°C oven for baking to remove the NMP liquid and leave a binder film. Finally, the resulting film is crushed using a pulverizer to obtain a binder powder.

[0103] (2) Use tetrahydrofuran (THF) as solvent, set column temperature (25°C to 40°C), flow rate (0.5 mL / min),

[0104] Configure the detector: differential refractive index detector (RI), inject the polymer sample into the system, record the sample chromatogram, obtain the retention time and detector response, and convert the sample retention time into molecular weight according to the calibration curve. Then calculate the number average molecular weight and weight average molecular weight, and calculate the polydispersity index.

[0105] Example 1-1

[0106] <Preparation of Electrolyte>

[0107] In an argon atmosphere glove box with a water content of less than 10 ppm, ethyl methyl carbonate and ethyl acetate were mixed in a mass percentage of 1:1 to prepare a base solvent, and then lithium salt lithium hexafluorophosphate (LiPF6) was added. Based on the total mass of the electrolyte, the mass percentage of LiPF6 was 12.5%, and the remainder was the base solvent.

[0108] <Preparation of positive electrode sheet>

[0109] Lithium cobalt oxide, conductive carbon SP, binder, and phenolic resin were mixed in a mass ratio of 97.5:1.1:1.3:0.1, and then N-methylpyrrolidone was added as an organic solvent and stirred evenly to prepare a positive electrode slurry with a solid content of 70%. The positive electrode slurry was evenly coated on the upper and lower surfaces of the positive electrode current collector aluminum foil with a thickness of 9μm, and then dried and pressurized and cut into a specified size to obtain a positive electrode sheet. The single-sided coating density of the binder is 0.129mg / mm 2 .

[0110] <Preparation of negative electrode sheet>

[0111] Artificial graphite, sodium carboxymethyl cellulose, negative electrode conductive agent, and styrene-butadiene rubber were mixed in a mass ratio of 95:2:1:2, and then distilled water was added as a solvent and stirred evenly to prepare a negative electrode slurry with a solid content of 45wt%. The negative electrode slurry was evenly coated on the upper and lower surfaces of a negative electrode current collector copper foil with a thickness of 6μm, and then dried and pressurized and cut into a specified size to obtain a negative electrode sheet.

[0112] <Isolation film>

[0113] A porous polyethylene film with a thickness of 15 μm was used as the separator.

[0114] <Preparation of lithium-ion batteries>

[0115] The prepared positive electrode sheet, separator, negative electrode sheet and separator are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly. After welding the pole ear, the electrode assembly is placed in an aluminum plastic film packaging bag, placed in a vacuum oven at 85°C for 12 hours to remove moisture, and the prepared electrolyte is injected. After vacuum packaging, standing, formation, shaping, and capacity testing, a lithium-ion battery is obtained.

[0116] Example 1-2 to Example 1-26

[0117] Except for adjusting the relevant parameters of the first polymer in the binder according to Table 1, the rest is the same as Example 1-1.

[0118] Comparative Examples 1 to 5

[0119] Except for adjusting the relevant parameters of the first polymer in the binder according to Table 1, the rest is the same as Example 1-1.

[0120] Table 1

[0121]

[0122]

[0123] Note: In Table 1 and the subsequent Tables 2 and 3, “whether there is a characteristic peak” refers to the peak at 1100 cm -1 ~1300cm -1 Is there any characteristic peak?

[0124] Example 2-1 to Example 2-6

[0125] Except for adjusting the content of the binder according to Table 2, the rest is the same as Example 1-26.

[0126] Table 2

[0127]

[0128] Example 3-1 to Example 3-6

[0129] Except for adjusting the single-sided coating density of the adhesive according to Table 3, the rest is the same as Example 1-26.

[0130] Table 3

[0131]

[0132] As can be seen from the table, the binder in this application has good bonding force and low swelling rate, which can reduce the expansion rate of the positive electrode sheet and improve the energy density of the secondary battery. In particular, when the mass content of the binder is 0.4% to 2%, or the coating density of the binder is 0.129 mg / mm 2 ~0.228mg / mm 2 The energy density of the secondary battery is higher.

[0133] The above are only embodiments of the present application and are not intended to limit the scope of protection of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the scope of protection of the present application.

Claims

1. A binder, characterized in that: It includes a first polymer, which includes a structure shown in the following formula I: wherein R1 is a C5-C12 straight-chain alkyl group, R2 is any one of a C1-C3 alkyl group, a hydrogen atom or an aryl group; the number average molecular weight of the first polymer is 6x10 4 ~2x10 6 .

2. The adhesive according to claim 1, characterized in that It satisfies at least one of the following conditions: (1) R1 is a C5-C8 alkyl group; (2) R2 is any one of a C1-C3 alkyl group or a hydrogen atom; (3)500≤m≤20000; (4)300≤n≤10000; (5) 1.25n≤m≤3n; (6) The number average molecular weight of the first polymer is 3×10 5 ~2x10 6 .

3. The adhesive according to claim 2, characterized in that It satisfies at least one of the following conditions: (1)800≤m≤13960; (2)400≤n≤10000。 4. The adhesive according to any one of claims 1 to 3, characterized in that The polydispersity of the first polymer is 1.3 to 1.

5.

5. The adhesive according to any one of claims 1 to 3, characterized in that Based on infrared spectroscopy characterization, the first polymer has a -1 ~1300cm -1 There are characteristic peaks inside.

6. The adhesive according to claim 1, characterized in that The glass transition temperature of the first polymer is -45°C to -25°C.

7. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector, at least one surface of which is provided with a positive electrode active layer, and the positive electrode active layer comprises the binder according to any one of claims 1 to 6.

8. The positive electrode sheet according to claim 7, characterized in that: Based on the mass of the positive electrode active layer, the mass content of the binder is a%, and 0.5≤a≤2.

9. The positive electrode sheet according to claim 8, characterized in that: The positive electrode active layer further comprises a positive electrode active material and a positive electrode conductive agent. The positive electrode conductive agent is attached to the surface of the positive electrode active material. The coverage rate of the positive electrode conductive agent on the surface of the positive electrode active material is S%, and 73.6+2a≤S<83.

7.

10. The positive electrode sheet according to claim 9, characterized in that: The positive electrode active material contains transition metal elements.

11. The positive electrode sheet according to claim 10, characterized in that: The transition metal includes at least one of nickel, cobalt or manganese.

12. The positive electrode sheet according to claim 7, characterized in that: On at least one surface of the positive electrode sheet, the coating density of the binder is 0.129 mg / mm 2 ~0.228mg / mm 2 .

13. A secondary battery, characterized in that: It comprises the positive electrode sheet as described in any one of claims 7 to 12.

Citation Information

Cited By

  • Binder, positive electrode sheet and secondary battery

    WO2026113524A1